PENGARUH INVESTASI TERHADAP PENYERAPAN TENAGA KERJA DI JAWA TENGAH TAHUN 2009-2013 - Abdul Haris Romdhoni (Jurnal Ilmiah Ekonomi Islam, 2017)
This study aims to determine the effect of investment on employment in Central Java in 2009-2013. As it is known that investment plays an important role in the absorption of labor or can reduce unemployment. Thus with the increased investment hence the absorption of labor will also increase. The research method used in this research is quantitative research method. This research was conducted in Central Java. The test used is the instrument using the validity test. Methods of data analysis using multiple linear regression analysis, classical assumption test. The results of this study indicate that the increase can be explained by the regression equation is Y = 16595732.325 + 0.32 X. Where the constant is positive value of 16595732.325 indicates that if the investment variable is considered constant (0), then the value of labor absorption of 16595732,325 . Then the regression coefficient of the investment variable is 0.32, this means that if the investment is increased one unit, it will increase the labor absorption of 0.32.